HUBUNGAN TINGKAT KETERGANTUNGAN MEROKOK DENGAN KEJADIAN PPOK DI PUSKESMAS TANJUNG SENGKUANG - Sri Linda Hartati; T. Eltrikanawati; Desy Desy (Ensiklopedia of Journal, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is the fourth leading cause of death worldwide, with around 3.5 million deaths recorded in 2021 (5%). The main cause is smoking dependence, which is prevalent in the community and increases the risk of respiratory infections, heart attacks, lung cancer, and depression. This study aims to determine the relationship between the level of smoking dependence and the incidence of COPD in the working area of the Tanjung Sengkuang Community Health Center. This research used an observational analytic method with a cross-sectional design and involved 48 respondents selected through Simple Random Sampling. Most respondents were male, aged 49 years, and had smoked for more than 10 years. The highest smoking dependence level was in the heavy category (43.8%), and the most frequent COPD incidence was in the severe impact category (39.6%). The Spearman rank test obtained a p-value of 0.022 (0.05), indicating a significant relationship between smoking dependence level and COPD incidence. It is recommended that COPD sufferers stop smoking, follow medical treatment, engage in light physical activity, maintain a clean diet and environment, and undergo regular check-ups to prevent exacerbations and improve their quality of life. Keywords: Chronic Obstructive Pulmonary Disease, Smoking Dependence Level